Exclusive olive oil consumption has a protective effect on coronary artery disease; overview of the THISEAS study. Issue 6 (30th July 2015) - Dimitriou, Maria; Rallidis, Loukianos S; Theodoraki, Eirini V; Kalafati, Ioanna Panagiota; Kolovou, Genovefa; Dedoussis, George V
Abstract: Objective: The aims of the current report are to present the demographic characteristics, clinical characteristics/biochemical indices and lifestyle habits of the population and to explore the potential association of exclusive olive oil consumption, in relation to lifestyle factors, with coronary artery disease risk. Design: Demographic, lifestyle, dietary and biochemical variables were recorded. Logistic regression analysis was performed in order to estimate the relative risks of developing coronary artery disease. Setting: The Hellenic study of Interactions between Single nucleotide polymorphisms and Eating in Atherosclerosis Susceptibility (THISEAS), a medical centre-based case–control study conducted in Greek adults. Subjects: We consecutively enrolled 1221 adult patients with coronary artery disease and 1344 adult controls. Results: A higher prevalence of the conventional established risk factors was observed in cases than in controls. Physical activity level was higher in controls (1·4 (sd 0·2) than in cases (1·3 (sd 0·3); P <0·001). Regarding current and ex-smokers, the case group reported almost double the pack-years of the control group (54·6 (sd 42·8) v . 28·3 (sd 26·3), respectively; P <0·001). Exclusive olive oil consumption was associated with 37 % lower likelihood of developing coronary artery disease, even after taking into account adherence to the Mediterranean diet (OR=0·63; 95 % CI 0·42, 0·93; P= 0·02). Conclusions: Exclusive olive oil consumption was associated with lower risk of coronary artery disease, even after adjusting for adoption of an overall healthy dietary pattern such as the Mediterranean diet.